1997
DOI: 10.1080/03079459708419234
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of organ cultures from chicken tissues for strains of infectious bronchitis virus isolated from the intestine

Abstract: SUMMARYOrgan cultures were prepared from various levels of intestine and kidney of 2 to 4-week old specific-pathogen-free chickens, and their susceptibility to ten strains of infectious bronchitis virus isolated from the chicken intestine and the Massachusetts strain M41 was investigated. The ability of a virus to grow depended on the strain of virus and size of the inoculum. While proventriculus, bursa and kidney were found to be universally susceptible to all viruses tested, some strains did not grow in caec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, susceptibility of these organs to IBV can be influenced by the strain of the virus and the amount of virus presence in the sample (infective dose). While a study suggested the universality of using kidney, bursa, and proventriculus in growing IBV, a poor result was obtained when IBV was propagated in cultures derived from different intestinal segments [ 61 ]. An advantage of this method includes easy titration and serotyping of IBV, since no virus adaptation is required [ 62 ].…”
Section: Diagnosismentioning
confidence: 99%
“…However, susceptibility of these organs to IBV can be influenced by the strain of the virus and the amount of virus presence in the sample (infective dose). While a study suggested the universality of using kidney, bursa, and proventriculus in growing IBV, a poor result was obtained when IBV was propagated in cultures derived from different intestinal segments [ 61 ]. An advantage of this method includes easy titration and serotyping of IBV, since no virus adaptation is required [ 62 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Several strains of IBV have been isolated from cloacal swabs, faeces and caecal tonsils Alexander et al, 1978;Cook, 1984;Lucio & Fabricant, 1990). In vitro explants of several gut tissues have been shown to support the growth of IBV (Bhattacharjee, 1994;Bhattacharjee & Jones, 1997;Darbyshire et al, 1976). In studies where virus isolation was attempted from several tissues, maximum virus isolations were obtained from the oesophagus of chickens infected with ECV2, an enteric isolate of IBV (Lucio & Fabricant, 1990) and 793/B-like virus (Dhinakar Raj & Jones, 1996a).…”
Section: Virus In the Intestinementioning
confidence: 99%
“…IBV has a short incubation period 6 , and viral spread occurs rapidly among chickens by aerosol and mechanical means 10 , 11 . IBV has the capability to multiply in various epithelial tissues, such as trachea 12 , 13 , kidney 14 , intestine 15 , 16 , spleen 17 and oviduct 16 , 18 20 . The virus is well known for its effects in laying hens, including egg production and quality drops 10 , 16 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%